International cooperation in the conditions of the NCTS joint transit system : in Ukrainian dimension - Fostolovych, Valentyna; Mykhalchyshyna, Larysa; Simanaviciene, Zaneta (Public Policy and Accounting, 2023)
The purpose of the study was to determine the main aspects of simplifying conditions and creating prospects for international cooperation in terms of Ukraine's participation in the NCTS joint transit system. Examining the data of the State Customs Service of Ukraine and the State Statistics Service of Ukraine, the intensive work of the subjects of the regime of the joint transit system during the period of NCTS in Ukraine was noted. Confirm the need to simplify the conditions for the international movement of goods, analysis of the growth dynamics of Ukraine's foreign trade. According to the results of the research, it was revealed that by applying the provisions of the Convention, the prevention of fraud with accompanying documents is implemented, the security of international transportation is increased and uniform forms of customs control are recognized by all 36 participating countries. After analyzing the benefits for the subjects of the customs regime, a decrease in the cost of customs procedures was noted; saving time on the duration of customs procedures; unloading checkpoints in queues; acceleration of the flow of trade in the international trade system. The whole model of work in the NCTS system is an innovative approach and needed a lot of work and transformation of the work of both the State Customs Service of Ukraine itself and the regulation of regulatory support. The condition of mandatory financial guarantee and sealing of all movements became the basis for the development of a new mechanism for the implementation of these procedures that meet the requirements of the Convention. The practical application of the processed results is carried out in stages. To date, the implementation of appropriate IT solutions based on MASP-C is already being implemented. Gradually, the technology of administration of customs payments is being improved and the Customs Code of Ukraine is being brought into line with the Customs Code of the EU.